2018
DOI: 10.3892/ol.2018.8387
|View full text |Cite
|
Sign up to set email alerts
|

Testes‑specific protease 50 as an independent risk factor for poor prognosis in patients with non‑small cell lung cancer

Abstract: Testes-specific protease 50 (TSP50) is normally expressed in the testes and is overexpressed in various types of human cancers, including breast cancer, colorectal carcinoma and laryngocarcinoma. However, little has been reported on the association between TSP50 and non-small cell lung cancer (NSCLC). The present study aimed to detect TSP50 expression in 198 strict follow-up cases of paired NSCLC and 15 cases of normal lung parenchymal specimens using immunohistochemical staining. The expression levels of TSP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…TSP50 is abnormally highly expressed in various tumor tissues, but is absent in normal tissues 16 20 , suggesting a pathogenic role for TSP50 in cancers. TSP50 levels appear to have important clinical implications for cancer patients 18 , 23 , 56 , therefore, we evaluated TSP50 transcription levels via UALCAN database. Analysis results revealed that mRNA expression of TSP50 was significantly higher in TCGA-LIHC tissues than in adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…TSP50 is abnormally highly expressed in various tumor tissues, but is absent in normal tissues 16 20 , suggesting a pathogenic role for TSP50 in cancers. TSP50 levels appear to have important clinical implications for cancer patients 18 , 23 , 56 , therefore, we evaluated TSP50 transcription levels via UALCAN database. Analysis results revealed that mRNA expression of TSP50 was significantly higher in TCGA-LIHC tissues than in adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the median survival times of patients with BORIS-sf6 overexpression or low expression were 26 weeks and 209 weeks, respectively; thus, BORIS-sf6 acts as a powerful prognostic predictor for lung cancer. TSP50 expression levels are higher in the advanced TNM stage in lung cancer patients ( 90 ). Kaplan−Meier analysis shows that disease-free survival and overall survival were significantly lower in lung patients with overexpressed TSP50 compared with those with low TSP50 expression, implying that TSP50 overexpression is associated with poor prognosis in lung cancer patients.…”
Section: Ctas As Biomarkers For Lung Cancer Diagnosis and Prognostic ...mentioning
confidence: 99%
“…TSP50 participated in multiple malignant processes of cancer, including stimulating cell proliferation via inhibiting activin signaling 269 , promoting invasion and metastasis by inducing EMT 270 . It was also discovered as a potential predictor of early recurrence and poor prognosis in malignancies 271 , and as a unique biomarker or treatment target for a variety of cancer therapies 272 , 273 , 274 , 275 .…”
Section: Protease-responsive Nanodds For the Targeted Theranostics Of Malignancymentioning
confidence: 99%